The Impact of Children on Parental Purchasing Behavior - Khan, Azhar; Gul, Shabana; Nisar, Muhammad; Hanan, Fazal; Ullah, Mohib; Nadir, Farah (The journal of contemporary issues in business and government, 2021)
Children have a major influence on their parents' purchases of similar products. Children are a dominant market for marketers to consider when making strategy choices since they are part of a family unit. This market is active in three ways: first, it is a large market in and of itself; second, it is a key influencer in facilitating purchasing decisions; and third, it is a possible future market. The focus of this research is on children's second position. They become the focal point of family expectations, and parents are more receptive to their recommendations when making purchases. This research study explains the effect of children on parental purchase behavior in the twin cities of Islamabad and Rawalpindi using a survey as a data collection method. Parents are among the participants in this research. The relationship between parental purchase behavior (PPB) and age of child (AOC), importance of child (IOC), product category (PC), communication pattern (CP), and family orientation is revealed by multiple regression analysis (FO). The age of the child (AOC), family orientation (FO), and Product Category (PC) are the three most significant factors that affect parental buying behavior. The paper concludes that children have a major influence on their parents' decisions.